An exploration into the use of webinjects by financial malware - Forrester, Jock Ingram (Rhodes University, Faculty of Science, Department of Computer Science, 2014)
As the number of computing devices connected to the Internet increases and the Internet itself becomes more pervasive, so does the opportunity for criminals to use these devices in cybercrimes. Supporting the increase in cybercrime is the growth and maturity of the digital underground economy with strong links to its more visible and physical counterpart. The digital underground economy provides software and related services to equip the entrepreneurial cybercriminal with the appropriate skills and required tools. Financial malware, particularly the capability for injection of code into web browsers, has become one of the more profitable cybercrime tool sets due to its versatility and adaptability when targeting clients of institutions with an online presence, both in and outside of the financial industry. There are numerous families of financial malware available for use, with perhaps the most prevalent being Zeus and SpyEye. Criminals create (or purchase) and grow botnets of computing devices infected with financial malware that has been configured to attack clients of certain websites. In the research data set there are 483 configuration files containing approximately 40 000 webinjects that were captured from various financial malware botnets between October 2010 and June 2012. They were processed and analysed to determine the methods used by criminals to defraud either the user of the computing device, or the institution of which the user is a client. The configuration files contain the injection code that is executed in the web browser to create a surrogate interface, which is then used by the criminal to interact with the user and institution in order to commit fraud. Demographics on the captured data set are presented and case studies are documented based on the various methods used to defraud and bypass financial security controls across multiple industries. The case studies cover techniques used in social engineering, bypassing security controls and automated transfers.
Keywords: Malware (Computer software) -- Analysis; Internet fraud; Computer crimes; Computer security; Electronic commerce